2020
DOI: 10.20944/preprints202003.0139.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review of Gamification Applied to Phishing

Abstract: Phishing is a set of devastating techniques which lure target users to provide critical resources. They are successful because they rely on human weaknesses. Gamification which is a recent and non-traditional learning method with purpose to motivate and engage user to carry out activities, is more and more applied to prevent such cyber threats. This paper provides the first survey of gamified solutions dedicated to educate against phishing from 2007 to 2019. The investigation is conducted on eight proposals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Although Quizizz.com was not created expressly for vocabulary study, the gamified components appeared to help students' vocabulary learning, as seen by the tight correlations between asynchronous mode scores and in-class learning outcomes. Following previous research (Li et al, 2014;Tchakounté et al, 2020;Zichermann & Cunningham, 2011), these findings suggest that online gamified quizzes can help improve traditional vocabulary teaching methods, increase learners' lesson participation in an asynchronous mode of learning, and improve students' learning outcomes in class.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Although Quizizz.com was not created expressly for vocabulary study, the gamified components appeared to help students' vocabulary learning, as seen by the tight correlations between asynchronous mode scores and in-class learning outcomes. Following previous research (Li et al, 2014;Tchakounté et al, 2020;Zichermann & Cunningham, 2011), these findings suggest that online gamified quizzes can help improve traditional vocabulary teaching methods, increase learners' lesson participation in an asynchronous mode of learning, and improve students' learning outcomes in class.…”
Section: Discussionsupporting
confidence: 72%
“…The results of the paired-sample t-test showed that there was a notable difference, with post-test scores being considerably higher than pre-test levels, and students expressing good views towards the gamified quiz. Moreover, in previous empirical investigations, a gamified quiz has been advised to reduce test anxiety and boost test performance (Pitoyo, 2019;Tchakounté et al, 2020). This is due to the fact that gamification is associated with increased engagement and enjoyment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations